2020
DOI: 10.2174/1573403x15666190321141856
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Hemodynamic Regulation and Cardiovascular Adaptations to Dynamic Exercise

Abstract: Exercise is a major challenge for cardiovascular apparatus since it recruits chronotropic, inotropic, pre-load, and afterload reserves. Regular physical training induces several physiological adaptations leading to an increase in both cardiac volume and mass. It appears that several genderrelated physiological and morphological differences exist in the cardiovascular adjustments and adaptations to dynamic exercise in humans. In this respect, gender may be important in determining these adjustments and adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 95 publications
2
39
1
Order By: Relevance
“…Moreover, studies have shown that dynamic aerobic exercise training does not change arterial blood pressure in male [32] and female [19] normotensive rats. Indeed, in the present study, the AP values obtained did not change after aerobic exercise training in both sexes; however, the female animals showed lower vascular sympathetic modulation than males, which may explain a reduced vasoconstriction and a lower vascular resistance in females in comparison to males, especially after exercise [33]. Interesting, we observed a positive correlation between LF band of SAP and SAP, showing that, despite similar basal values of AP between sexes and condition of training, animals with lower sympathetic vascular modulation presented reduced values of SAP.…”
Section: Discussioncontrasting
confidence: 49%
“…Moreover, studies have shown that dynamic aerobic exercise training does not change arterial blood pressure in male [32] and female [19] normotensive rats. Indeed, in the present study, the AP values obtained did not change after aerobic exercise training in both sexes; however, the female animals showed lower vascular sympathetic modulation than males, which may explain a reduced vasoconstriction and a lower vascular resistance in females in comparison to males, especially after exercise [33]. Interesting, we observed a positive correlation between LF band of SAP and SAP, showing that, despite similar basal values of AP between sexes and condition of training, animals with lower sympathetic vascular modulation presented reduced values of SAP.…”
Section: Discussioncontrasting
confidence: 49%
“… 11–13 19 24 To our knowledge, existing research and its application to female athletes has been generalised from male data, despite limited research indicating significant sex differences and responses of HRV and the ANS. 5 12 13 This generalisation is a significant misstep for female athletes as the neural control of circulation differs with sex, mainly attributed to the effects of ovarian hormones on ANS. 8 16 23 25 26 Moreover, endogenous and exogenous hormones exert different modulatory effects; specific to the progestogen of the exogenous hormone formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout each phase, fluctuations in hormones trigger not only changes in the reproductive system, but also in all the tissues of the body, 1 modulating sleep, 2 3 circadian rhythms 4 and the autonomic nervous system (ANS). [5][6][7] For instance, there is evidence of a…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, even though our model did not allow the three-way statistical analysis, from Figure 3 it can be observed a difference between ethnic groups: Nepalese porters may have required a higher blood flow increment after exercise in altitude, both in the forearm and in the thigh muscle. The marked hemodynamic response to submaximal dynamic exercise, as found in the present study, might be further characterized in terms of hemodynamic reserves (Bassareo and Crisafulli, 2020): hypoxia has a role in muscle metaboreflex (Mulliri et al, 2019), and the dynamics of diverse muscle groups can be stressed to achieve further insight. This response might be the result of systemic advantage, achieved by heritable factors or due to long-term adaptation, representing a likely basis for a further adaptation in exercised muscles.…”
Section: Discussionmentioning
confidence: 63%